The Role of Non-Mycorrhizal Fungi in Germination of the Mycoheterotrophic Orchid Pogoniopsis schenckii Cogn. - Sisti, Laís Soêmis; Flores-Borges, Denisele Neuza Aline; Andrade, Sara Adrián López de; Koehler, Samantha; Bonatelli, Maria Letícia; Mayer, Juliana Lischka Sampaio (Frontiers in Plant Science, 2019)
Endophytic fungi are those that inhabit within organs and tissues without causing damage, while mycorrhizal fungi develop hyphal complexes called pelotons within cortical cells of orchid roots. Although abundant and frequent in all plant organs, the role of endophytic fungi has been neglected in relation to orchid’s early development. Pogoniopsis schenckii Cogn. is an aclorophyllated and mycoheterotrophic (MH) orchid. This study aimed at i) investigating the endophytic fungal community in organs of P. schenckii and its mycorrhizal fungi associated; ii) evaluating the ability of isolated fungus in the in vitro germination of the seeds of the species, and iii) describing the development of P. schenckii protocorm, analyzing the ultrastructure of the infected cells. Six genera of fungi were isolated and identified through the partial sequencing of the internal transcribed spacer region, all belonging to the phylum Ascomycota. Also, Tulasnellaceae was identified through uncultured technique as potentially mycorrhizal in this MH orchid. Some isolates of the genera Trichoderma, Fusarium, and especially Clonostachys presented germinative potential on P. schenckii seeds, causing rupture of the external tegument. The protocorms showed complete absence of peloton formation, but fungal hyphae were clearly observed within living cells. This is the first report of germination of a MH and aclorophyllated orchid species stimulated by the presence of non-mycorrhizal endophytic fungi isolated from fruits and roots of the same species.